Endometrial Fluid study for prevalence of tuberculosis by testing for diagnosis by CB NAAT culture (Panacea Journal of Medical Sciences, 2022)
Background: The frequency of Genital TB is 0.69% in evolved nations and 19% in non-industrial nations. The fallopian tube is most regularly influenced followed by endometrium and cervix. It is optional to TB concentrate somewhere else in body brought about by Mycobacterium Tuberculosis. History of essential fruitlessness in a lady whose assessment uncovers no evident reason and gives family ancestry or individual history of TB emerges doubt of genital TB.Objective: 1: To study the prevalence rate and risk factors for endometrial TB in infertile females; 2: To study clinical and reproductive profile of women diagnosed with endometrial TB; 3: To study the importance of CB NAAT over other diagnostic tests in diagnosing TB.Design: Hospital based cross sectional study done on 100 subjects for one and a half year (June 2017 to July 2019).Setting: Labour room. Minor OT. OPDProcedure: 2-5 ml endometrial fluid was retrieved on day 1/2 of menses using pipelles cannula. It was transferred to falcon tube and CB NAAT analysis was done using cartridge.Results: Out of 100 cases, 4 were detected to be positive for endometrial TB. Out of them, 3 fell in age group of 30-39 years; all belonged to upper middle socioeconomic status. 3 cases had achieved menarche at >14 years of age and one had oligomenorrhoea.Outcome Measure: Number of patients testing positive for endometrial TB by CB NAAT Culture.Conclusion: Genital TB is a major cause of infertity and is generally underestimated because of asymptomatic nature of infection and diagnostic challenges. Large multicentric studies are needed to estimate the magnitude of female genital TB. Our study confirmed the usefulness of CB NAAT compared to Chest X-ray and smear microscopy for early diagnosis of suspected endometrial TB. Its simplicity, sensitivity, speed and automation makes this technique a very attractive tool for diagnosis of mycobacterial TB.